Supply and Demand Analysis of Ecotourism Potency at Danau Linting, Village of Sibunga-bunga Hilir, Subdistrict of STM Hulu, Regency of Deli Serdang - Marthalena Ginting; Pindi Patana; Agus Purwoko (Peronema Forestry Science Journal, 2013)
Danau Linting is one of hotspring lake in North Sumatera that has potential to be developed as ecotourism, although there is no serious management from local government. Data was collected through questionnaires, observation and literature study. These data  were analyzed with descriptive analysis, scoring analysis, and supply and demand analysis so that arranged strategy of ecotourism development.  Supply and demand aspects were scored by tourist such as tourist attraction, amenity and accessibility. Visitor’s assesment of supply aspect was categorized as worst to middle, while demand aspect was categorized as middle to important, that means most of visitors assumed that this region was important and useful so that we need better management. Key words: Danau Linting, Ecotourism potency, analysis of supply and demand